Peran Guru Bimbingan dan Konseling Pada Pembelajaran Berbasis Deep Learning Untuk Meningkatkan Self-Regulated Siswa Generasi Z - Suhendri, Suhendri; Ajie, Gregorius Rohastono; Mei Fita Asri Untari (Perkumpulan Kualitama Edukatika Indonesia, 2025)
Increasing the role and competence of Guidance and Counseling Teachers in implementing Deep Learning to develop the potential of Generation Z is an important effort in facing educational challenges in the digital era. Generation Z, with its unique characteristics and different learning needs, requires innovative and relevant learning approaches. The solution implemented is to carry out workshop activities related to Deep Learning to improve student self-regulation as a learning method that emphasizes deep understanding and application of knowledge, offering great potential to meet the needs and active involvement of students in learning activities. However, the implementation of Deep Learning in schools in Indonesia still faces various obstacles. One of the causes is the lack of understanding and skills of counseling teachers in applying the deep learning approach. The method of implementing this community service program activity was carried out for 2 weeks which was divided into three stages, namely: (1) planning stage, (2) implementation stage, (3) evaluation stage. The training to increase the role of guidance and counseling teachers conducted by the Team showed success in increasing the understanding of counseling teachers, especially in the application of deep learning approaches or methods in counseling services. BK teachers are able to have an understanding and are able to implement the concept of deep learning in BK. This will have a positive impact on the implementation of counseling services.